2008
DOI: 10.1111/j.1939-1676.2007.0017.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Evaluation of Carboplatin in Tumor‐Bearing Cats: A Veterinary Cooperative Oncology Group Study

Abstract: Background: The dosage of carboplatin in cats has been reported anecdotally and experimentally in non-tumor-bearing cats, but the dosage for carboplatin treatment in tumor-bearing cats has yet to be defined in a prospective clinical trial.Purpose: To determine the maximally tolerated dose (MTD) and dose-limiting toxicosis (DLT) of carboplatin in tumorbearing cats.Cats: Fifty-nine cats with measurable solid tumors. Methods: The starting dose of carboplatin was 160 mg/m 2 of body surface area IV. Doses were incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 13 publications
0
54
0
3
Order By: Relevance
“…Additional modifications can be made as necessary in patients in which toxicity is a problem so that quality of life is maintained during treatment. Chemotherapy can be used before (neoadjunctive) or after (adjunctive) surgery for solid tumours and occasionally as a sole agent in the palliative setting (Page and others 1993, Chun and others 1997, Bacon and others 2008, Bailey and others 2008, Bulakowski and others 2008, Grant and others 2008, Kisseberth and others 2008, Rassnick and others 2008, Cooper and others 2009, Dominguez and others 2009, Lori and others 2010, Arnold and others 2011, Fidel and others 2011, Bray and Polton 2014, Selmic and others 2014, Cannon and others 2015, Culp and others 2015, Marconato and others 2015) (Table 5). Intracavitatory chemotherapy can be useful in some patients with neoplastic pleural effusion (Charney and others 2005); permanent pleural ports are well tolerated and facilitate delivery as well as allowing drainage of the effusion.…”
Section: Chemotherapymentioning
confidence: 99%
“…Additional modifications can be made as necessary in patients in which toxicity is a problem so that quality of life is maintained during treatment. Chemotherapy can be used before (neoadjunctive) or after (adjunctive) surgery for solid tumours and occasionally as a sole agent in the palliative setting (Page and others 1993, Chun and others 1997, Bacon and others 2008, Bailey and others 2008, Bulakowski and others 2008, Grant and others 2008, Kisseberth and others 2008, Rassnick and others 2008, Cooper and others 2009, Dominguez and others 2009, Lori and others 2010, Arnold and others 2011, Fidel and others 2011, Bray and Polton 2014, Selmic and others 2014, Cannon and others 2015, Culp and others 2015, Marconato and others 2015) (Table 5). Intracavitatory chemotherapy can be useful in some patients with neoplastic pleural effusion (Charney and others 2005); permanent pleural ports are well tolerated and facilitate delivery as well as allowing drainage of the effusion.…”
Section: Chemotherapymentioning
confidence: 99%
“…Carboplatin ( cis ‐diammine‐1,1‐cyclobutane decarboxylate platinum (II) carboplatin) is a second generation platinum chemotherapy agent that is used in a variety of tumours in dogs and cats (Page and others 1993, Kisseberth and others 2008). Phase I clinical trials have been performed in both dogs and cats, and a maximum toxic dose and suggested dosing schedule have been established in both species (Page and others 1993, Kisseberth and others 2008). Reported dosing regimes are 300 mg/m2 intravenously every 3 weeks in dogs, and 200 to 240 mg/m2 intravenously every 28 days in cats (Hahn and others 1997, Kisseberth and others 2008).…”
Section: Introductionmentioning
confidence: 99%
“…20 Preliminary response data from this study found an 11.9% overall response rate after a single dose of carboplatin. 20 However, doses of carboplatin administered in that study were lower than the generally recommended dosing schemes, owing to the phase 1 nature of the trial. To continue, reported response rate assessment only included a single dose of the drug; thus, maximal responses may not have been achieved in patients who received only one treatment.…”
Section: Discussionmentioning
confidence: 69%
“…20 A phase 1 clinical trial of carboplatin in feline patients affected by various malignancies, including assorted carcinomas, reported that carboplatin at a dose of 240 mg/m 2 was safe and well tolerated in tumor-bearing cats. 20 Preliminary response data from this study found an 11.9% overall response rate after a single dose of carboplatin. 20 However, doses of carboplatin administered in that study were lower than the generally recommended dosing schemes, owing to the phase 1 nature of the trial.…”
Section: Discussionmentioning
confidence: 99%